Eskatologiese perspektiewe in die Nagmaal - Bingle, P. W. (Koers, 1990)
Eschatological perspectives in Holy Communion. Eschatology reveals various perspectives concerning Holy Communion. Formulation, definition and the context of Holy Communion in the Scriptures have an eschatological setting. Due to the dovetailing of the old and the new aeon Holy Communion contains an eschatological tension; it projects an eschatological prefiguration; there is an eschatological solidity and adherence in Holy Communion, namely, the God of faith; an eschatological maturing process takes place in and through Holy Communion; there is an eschatological dimension with an existential moment in Holy Communion; there is an eschatological paranese in Holy Communion; eschatology projects an alignment with the judgement of God into Holy Communion and eschatology places Holy Communion in a missiological perspective. The remembrance of the perfecta fulfilled by Christ invokes the futura which is yet to come. The commemorative character of Holy Communion is more than a mere in memoriam of Christ’s death as Mediator. It is a remembrance of Jesus Christ, the risen Lord Himself By virtue of its sacramental nature. Holy Communion as a remembrance supper is a token and seal of the body and blood of the Mediator Jesus Christ the Lord - He who is the Eschatos will come as the Elpidos for time and eternity. This sacramental token and seat is also token and seal of the final eschaton when God will be all in all (cf 1 Cor 15:28).